Riccati Equations in Nash and Stackelberg Differential and Dynamic Games. Issue 1 (July 2017) - Başar, Tamer; Moon, Jun
Abstract: The purpose of this paper is to provide an overview of various types of Riccati differential and difference equations (RDEs) and the associated algebraic Riccati equations (AREs) that arise in various classes of linear quadratic (LQ) differential and dynamic games. We first study generalized RDEs and AREs in LQ zero-sum differential games, and then consider coupled RDEs and AREs in LQ nonzero-sum differential games. We also discuss some nonsymmetric RDEs in LQ Stackelberg differential games, and RDEs in LQ dynamic games.